Entre bois e cabras: uma visão histórica sobre mentalidades e valores nos sertões - Gonçalves Júnior, Oswaldo (Centro de Pesquisa e Documentação de História Contemporânea do Brasil da Fundação Getúlio Vargas, 2011)
A culture of resistance in the semi-arid, expressed by mentalities and values, goes against the economic potential of sheep and goat raising, considered as an inferior activity when compared to the cattle raising, historically linked to social status and prestige. This paper attempts to shed light on aspects that make possible to clarify the roots of the cognitive apparatus that supports this view, resorting to it to the production of relevant authors dealing with the issue of displacement of colonizer and livestock in the hinterlands. Ultimately, it seeks evidence of the influence of the historical process of economic and social organization of space on the present.

Une culture de résistance dans le semi-aride, exprimée pour mentalités et valeurs, va contre le potentiel économique de l'élevage de caprins et d'ovins, vu de façon inférieur par rapport au bétail bovin, historiquement lié au prestige et au statut social. L'article cherche faire la lumière sur les aspects qui permettent clarifier les racines de l'appareil cognitif qui soutient ce point de vue, en utilisant comme recours la production des auteurs pertinents qui traitent du sujet du déplacement colonisateur et d'élevage au intérieur du pays. En fin de compte, il cherche les preuves de l'influence du processus historique de l'organisation économique et sociale de cet espace sur le présent.

Uma cultura de resistência no semi-árido, expressa por mentalidades e valores, incide contra o potencial econômico da caprinovinocultura, vista de maneira inferiorizada em relação à pecuária bovina, atrelada historicamente a prestígio e status social. O artigo procura lançar luz sobre aspectos que possibilitem tornar mais claras as raízes do aparato cognitivo que sustenta essa visão, recorrendo-se para isso à produção de autores relevantes que tratam do tema do deslocamento colonizador e da pecuária nos sertões. Em última análise, busca elementos da influência do processo histórico de organização econômica e social desse espaço sobre o presente.
Between cattle and goats: a historical view about mentalities and values in the Brazilian Northeastern backlands
Keywords: cattle raising; sheep and goat raising; Semi-arid; prestige; social status; pecuária; caprinovinocultura; semi-árido; prestígio; status social